Studi Literatur: Potensi Local Taman Nasional Gunung Lauser Bukit Lawang Sebagai Sumber Belajar Keanekaragaman Hayati - Priani, Nurul; Hutagaol, Jeklin; Jumiah, Jumiah; Sahila, Iza (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Biodiversity, also known as natural diversity, includes genetic and species differences, such as flora and fauna. Each region has biodiversity, one of which is Bukit Lawang, which has the Gunung Lauser National Park (TNGL), and various research on biodiversity has been carried out in Bukit Lawang. With this, there is local potential that can be developed through learning resources, where currently teachers are required to be creative and also link learning with the local potential of the area. So this article aims to review local potential as a source of learning, where this article uses the method of literature review by analyzing content and searching literature based on the last 7 years' publications. Based on the search results, there were 6 findings including survival plants, orchids, types of snakes, insects, orangutans, and microscopic fungi which belong to the 3 kingdoms namely Plantae, Animalia, and fungi. The findings carried out in the Gunung Lauser Bukit Lawang National Park are included in biology learning resources on biodiversity material in class X, these learning resources can make contextual learning for students.